Survey of ICT and Education in Africa : Eritrea Country Report - Hare, Harry (World Bank, Washington, DC, 2012)
This short country report, a result of larger Information for Development Program (infoDev)-supported survey of Information and Communication Technologies (ICT) in education in Africa, provides a general overview of current activities and issues related to ICT use in education in the country. Eritrea has made significant efforts to reform its education system with the objective of providing its citizens with accessible and high-quality education that is modern, technologically advanced and that will create an internationally competitive human resource. The rise in the gross enrolment rates, the construction of new classrooms and reconstruction of those destroyed, and the capacity-building initiatives at the Ministry of Education all are indications of a country that is ready to learn. The government's acknowledgement that ICT has a role to play in improving both access and quality of education is commendable given the bigger challenges of poverty, hunger, disease and access to basic education. The National ICT for Education Policy and the completion of the implementation master plan is bound to generate the necessary momentum within government and other education sector players to seriously start integrating ICTs into education.